Uma tríade botânica na paisagem oitocentista portuense: jardins e hortos de excelência científica e económica - Vieira, Cristiana; Antunes, Ana Catarina; Faria, Sónia (CEM – Cultura, Espaço & Memória, 2021)
The present work explores the recognition of the past and present genius loci of three spaces of Porto city center as remaining and transformed representations of spaces with distinct, interconnected and pertinent botanical missions in the nineteenth century landscape of the city. Through the exploration of sources left by the interveners or graphic testimonies of the urban landscape from 1850 to the present day of these (ethno-)botanical spaces, we explore how the interveners and spaces of the Jardim Botânico da Academia Polythecnica do Porto, the Horto-pharmacêutico da Botica da Hospital Real de Santo António and the Horto das Virtudes mutually influenced. On the other hand, it is demonstrated how these spaces determined a time of special interest in botany that would not be repeated in the history of the city and its population.